2022
DOI: 10.1021/acs.energyfuels.2c00814
|View full text |Cite
|
Sign up to set email alerts
|

NOx Adsorption Mechanism of Coal-Based Activated Carbon Modified with Trace Potassium: In Situ DRIFTS and DFT Study

Abstract: A series of coal-based materials were prepared using a hydrothermal method combined with high-temperature CO2 activation. During sample preparation, K modification was performed to optimize the surface functional groups and pore structure. The NO x adsorption volume of each sample was evaluated in a simulated flue gas atmosphere. The physical and chemical parameters of the samples were characterized by X-ray diffraction, X-ray photoelectron spectroscopy, Raman spectroscopy, and temperature-programmed desorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The first vibration band at 1260 cm −1 appeared at around 25 °C, reaching its maximum intensity at 100 °C, but disappearing at 275 °C, while the second one (1350 cm −1 ) was recorded from 275 to 500 °C. This low temperature band can be referred to bidentate nitrates, 41 while the high temperature band has been reported as monodentate nitrates. 42 These results match the NO-O 2 sorption process, followed by thermogravimetry (Figure 2).…”
Section: Resultsmentioning
confidence: 96%
“…The first vibration band at 1260 cm −1 appeared at around 25 °C, reaching its maximum intensity at 100 °C, but disappearing at 275 °C, while the second one (1350 cm −1 ) was recorded from 275 to 500 °C. This low temperature band can be referred to bidentate nitrates, 41 while the high temperature band has been reported as monodentate nitrates. 42 These results match the NO-O 2 sorption process, followed by thermogravimetry (Figure 2).…”
Section: Resultsmentioning
confidence: 96%
“…The D-band reflects the disorder and lattice defects in the graphite crystal structure, while the G-band arises from the vibration mode of the sp 2 hybridized carbon atoms in the graphite lattice, corresponding to the E 2g symmetry . The intensity ratio of the D-band to the G-band ( I D / I G ) is commonly used to estimate the disorder and crystalline structure in carbon materials . With an increase in metal loading, the I D / I G ratio gradually decreases, indicating a reduction in surface defects and an enhancement in the degree of graphitization .…”
Section: Results and Analysismentioning
confidence: 99%
“…26 The intensity ratio of the D-band to the G-band (I D /I G ) is commonly used to estimate the disorder and crystalline structure in carbon materials. 27 With an increase in metal loading, the I D /I G ratio gradually decreases, indicating a reduction in surface defects and an enhancement in the degree of graphitization. 28 Research has indicated that a lower degree of graphitization indicates a higher proportion of disordered carbon structures in the catalyst, which supports the formation of porous carbon materials.…”
Section: Xrd and Raman Analysismentioning
confidence: 99%
“…Wang et al 92 prepared AC from Zhundong coal using hydrochloric acid and nitric acid as activators and subsequently modified it with KOH. The results showed that the AC had the highest pore structure when the KOH content was 0.05 g KOH/ 30 mL H 2 O. Li et al 93 modified CAC by heat treatment, by sodium hydroxide impregnation, and by ammonia solution impregnation.…”
Section: Modification Of Cacmentioning
confidence: 99%